Spatio-temporal Analysis of Regional Systems: A Multiregional Spatial Vector Autoregressive Model for Spain - Julian Ramajo; Miguel A. Marquez; Geoffrey J.D. Hewings (European Regional Science Association (ERSA), 2013)
This paper contributes to the recent literature in spatial econometrics that focuses on space-time data modeling implementing a multi-location time-series statistical framework to analyze a regional system. Therefore, taking as a point of departure the Global Vector Autoregression approach introduced in Pesaran et al. (2004), a multiregional spatial vector autoregressive model (MultiREG-SpVAR) is formulated and then applied to study the spatio-temporal transmission of macroeconomic shocks across the regions in Spain. The empirical application analyzes the extent to which a region?s economic output growth is influenced by the growth of its neighbors (push-in or inward growth effect), and also investigates the relevance of spillovers derived from temporary region specific output growth shocks (push-out or outward growth effect). Our results identify some regions that perform as ?growth generating? within the Spanish regional system since growth shocks from these regions spill over to a large number of regions of the country, playing a key role in transmitting regional business cycles. The policy implications of our results suggest that national and/or regional governments should stimulate economic activity in these leading regions in order to favor the economic recovery process of the whole Spanish economy.
Keywords: 330; Regional growth; spatial econometrics; vector autoregressions; spillovers